Financial Openness and Income Inequality in Sub-Saharan Africa: The Moderating Roles of Development Level and Land Access - Mounoufié Valery KOFFI; Konan Abogni Augustin KOUADIO (Lafadz Jaya Publisher, 2025)
This study investigates the relationship between financial openness and income inequality in Sub-Saharan Africa, emphasizing the moderating roles of development level and access to land. While the literature provides mixed evidence on whether financial openness exacerbates or mitigates inequality, limited attention has been given to the transmission channels through which these effects operate, particularly in developing regions. Using a panel dataset of 38 Sub-Saharan African countries over the period 2010–2019, this study employs the system Generalized Method of Moments (GMM) to address endogeneity concerns and capture dynamic effects. The findings reveal a dual and asymmetric impact of financial openness. De facto financial openness—capturing actual cross-border financial flows—significantly reduces income inequality, whereas de jure openness—reflecting policy-based financial liberalization—tends to increase inequality. Importantly, the results demonstrate that access to land mitigates the inequality-enhancing effect of de jure openness, suggesting that land distribution plays a crucial redistributive role. Furthermore, the level of economic development amplifies the inequality-reducing impact of de facto openness, indicating that structural conditions shape the inclusiveness of financial integration. These findings contribute to the literature by integrating structural and resource-based channels into the financial openness–inequality nexus. From a policy perspective, the results highlight that financial liberalization alone is insufficient to ensure equitable outcomes; complementary policies promoting inclusive access to productive assets, particularly land, are essential. Strengthening institutional frameworks and addressing structural inequalities are therefore critical to maximizing the distributive benefits of financial openness in Sub-Saharan Africa.